Variations in basilic vein anatomy in patients undergoing haemodialysis access surgery: A cross-sectional study - Amna Riaz Khan; Zia Ur Rehman; Waryam Saleh (Journal of the Pakistan Medical Association, 2026)
Objective: To explore different anatomical variants of basilic veins in patients undergoing haemodialysis access surgery. Method: The descriptive, explorative, cross-sectional study was conducted from February 2023 to February 2024 at the Aga Khan University Hospital, Karachi, and comprised patients undergoing haemodialysis access surgery. Basilic vein anatomy was identified on preoperative ultrasound and documented with its type as type I = basilic vein joining brachial vein in the axilla, type II = basilic vein joining one of two brachial veins in mid/ lower arm. and type III = basilic vein joining single brachial vein in arm. Data was analysed using SPSS 19. Results: Of the 131 patients (200 limbs) with mean age 59.03+/-14.93 years, 68(51%)were males and 63 (48%) were females. Overall, 142(71%) limbs were diagnosed as having type I basilic vein, followed by 54(27%) type II and 4(2%) type III. There was no association noted for basilic vein anatomy with either gender or hand dominance (p>0.05). Conclusion: In patients undergoing haemodialysis access surgery, the most common type of basilic vein anatomy was type I Key Words: Brachio-Basilic transposition arteriovenous fistula, Dialysis access, Anatomical variation, Basilic vein